2017
DOI: 10.23922/jarc.2016-005
|View full text |Cite
|
Sign up to set email alerts
|

Rules for anal fistulas with scrotal extension

Abstract: Abstract:Objectives: To evaluate the rules for anal fistulas with scrotal extension, in particular, whether a high transsphincteric or suprasphincteric fistula, of which internal openings are usually located posteriorly, would extend into the scrotum. Methods: We retrospectively analyzed 446 consecutive male patients who underwent definitive anal fistula surgery. We compared fistulas with scrotal extension according to the location of the internal opening and divided them into anterior and posterior groups. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…We observed a signi cant correlation between the location of internal opening (anterior or posterior to the transverse anal line) and the stula type (p < 0.05). This is consistent with the previous reported [7,18] which showed that the majority of anal stulas extending into the scrotum were low transsphincteric stulas with the anterior internal opening. Also, high transsphincteric and suprasphincteric stulas usually had posterior internal openings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We observed a signi cant correlation between the location of internal opening (anterior or posterior to the transverse anal line) and the stula type (p < 0.05). This is consistent with the previous reported [7,18] which showed that the majority of anal stulas extending into the scrotum were low transsphincteric stulas with the anterior internal opening. Also, high transsphincteric and suprasphincteric stulas usually had posterior internal openings.…”
Section: Discussionsupporting
confidence: 94%
“…Goodsall's rule for predicting the trajectory of anal stulas is popular; however, the long-tract anterior stula, which may include stulas with scrotal extension, is an exception to this rule [7]. Magnetic resonance (MR) is extremely useful in these cases thanks to its capability to provide precise anal canal anatomy and the relation of the stula to perineal structures.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conjectured that all exceptions of the GR, wherein a long anterior fistula opening anteriorly will possibly be of a low variety, either intersphincteric or trans-sphincteric. In their series, there was no case of long anterior high suprasphincteric fistulas with anterior internal openings 1. Taken together, the above shows that anal fistulas opening in the midline raphe of the scrotum are rarely reported, are primarily of the low variety with no suprasphincteric extensions and open anteriorly in the anal canal.…”
Section: Descriptionmentioning
confidence: 86%
“…Goodsall’s rule (GR) states that if the external opening of an anal fistula is anterior to a transverse line across the anus will open radially into the anterior wall of the anal canal provided it is less than 3 cm from the anal verge, else it will open in the midline posteriorly 1. Exceptions to this rule have been reported for long anterior fistulas which instead of opening posteriorly in the midline as per the GR, opens anteriorly 2.…”
Section: Descriptionmentioning
confidence: 99%
“…The drainage seton band was removed 4-6 weeks after the operation. Healing of the anal fistula was confirmed when the wound was completely epithelialized, with no fluid collection apparent on MRI after the fistula was transected and the seton removed 8) . We named these procedures "MRI navigating seton" surgery.…”
Section: Surgical Proceduresmentioning
confidence: 99%